(untitled) (Current Horticulture, 2024)
An experiment was conducted during 2015-16 and 2016-17 at Agricultural Research Station, Banswara district of Rajasthan (Maharana Pratap University of Agriculture & Technology, Udaipur) to study the response of different agro-chemicals for growth and flowering of mango (Mangifera indica). The plants were planted in a square system of planting with a 10m x 10m spacing. Agro-chemicals, calcium chloride, potassium nitrate, paclobutrazol and sorbitol were used. The treatment combinations were applied as control (water spray), calcium chloride (0.3, 0.6 and 0.9%), potassium nitrate (1, 2 and 3%), paclobutrazol (500, 1000 and 1500 ppm) and sorbitol (1.5, 2.0 and 2.5%). Application of different agro-chemicals were applied at different stages and time. Effect of agro-chemicals was found significant for growth and flowering parameters. Paclobutrazol (1500 ppm) was found better for shoot length and diameter, tree spread, canopy volume and days of fruit setting from flower initiation and flowering characters viz. date of flower initiation, per cent fruit setting and retention, days to harvest from fruit setting and first flush after fruiting.